MERCURY-3: a randomized comparison of netarsudil/latanoprost and bimatoprost/timolol in open-angle glaucoma and ocular hypertension - Stalmans, Ingeborg; Lim, Kin Sheng; Oddone, Francesco; Fichtl, Marek; Belda, Jose I; Hommer, Anton; Laganovska, Guna; Schweitzer, Cédric; Voykov, Bogomil; Zarnowski, Tomasz; Holló, Gábor (Graefe's archive for clinical and experimental ophthalmology, 2024)
UNLABELLED: PURPOSE : To compare the efficacy and safety of the fixed-dose combination (FDC) of netarsudil 0.02%/latanoprost 0.005% ophthalmic solution (NET/LAT; Roclanda®) with bimatoprost 0.03%/timolol maleate 0.5% (BIM/TIM; Ganfort®) ophthalmic solution in the treatment of open-angle glaucoma (OAG) and ocular hypertension (OHT). METHODS: MERCURY-3 was a 6-month prospective, double-masked, randomized, multicenter, active-controlled, parallel-group, non-inferiority study. Patients (≥ 18 years) with a diagnosis of OAG or OHT in both eyes that was insufficiently controlled with topical medication (IOP ≥ 17 mmHg in ≥ 1 eye and < 28 mmHg in both eyes) were included. Following washout, patients were randomized to once-daily NET/LAT or BIM/TIM for up to 6 months; efficacy was assessed at Week 2, Week 4, and Month 3; safety was evaluated for 6 months. Comparison of NET/LAT relative to BIM/TIM for mean IOP at 08:00, 10:00, and 16:00 h was assessed at Week 2, Week 6, and Month 3. Non-inferiority of NET/LAT to BIM/TIM was defined as a difference of ≤ 1.5 mmHg at all nine time points through Month 3 and ≤ 1.0 mmHg at five or more of nine time points through Month 3. RESULTS: Overall, 430 patients were randomized (NET/LAT, n = 218; BIM/TIM, n = 212), and all received at least one dose of study medication. Efficacy analyses were performed at Month 3 on 388 patients (NET/LAT, n = 184; BIM/TIM, n = 204). NET/LAT demonstrated non-inferiority to BIM/TIM, with a between-treatment difference in IOP of ≤ 1.5 mmHg achieved at all time points and ≤ 1.0 mmHg at the majority of time points (six of nine) through Month 3. Mean diurnal IOP during the study ranged from 15.4 to 15.6 mmHg and 15.2 to 15.6 mmHg in the NET/LAT and BIM/TIM groups respectively, with no between-group statistically significant difference. No significant differences were observed in key secondary endpoints. No serious, treatment-related adverse events (AEs) were observed, and AEs were typically mild/moderate in severity. The most common treatment-related AEs were conjunctival hyperemia (NET/LAT, 30.7%; BIM/TIM, 9.0%) and cornea verticillata (NET/LAT, 11.0%; BIM/TIM, 0%). CONCLUSIONS: Once-daily NET/LAT was non-inferior to BIM/TIM in IOP reduction in OAG and OHT, with AEs consistent with previous findings. NET/LAT offers a compelling alternative FDC treatment option for OAG and OHT.
Keywords: Ocular Hypertension; Ophthalmic Solutions; výsledek terapie; Intraocular Pressure; Tonometry, Ocular; lidé; dvojitá slepá metoda; Timolol; glaukom s otevřeným úhlem; tonometrie oční; Treatment Outcome; beta-alanin; Glaucoma, Open-Angle; latanoprost; nitrooční tlak; prospektivní studie; Double-Blind Method; Bimatoprost; bimatoprost; benzoáty; Latanoprost; Prospective Studies; Benzoates; oční roztoky; timolol; Antihypertensive Agents; beta-Alanine; antihypertenziva; oční hypertenze; Humans